FITIK TAMİRİNDE FARKLI KATMANLARA KONULAN YAMA (PROLEN) TİP I VE TİP III KOLLAJEN FORMASYONUNU ETKİLİYOR MU? - YUR, MESUT (Fırat Üniveristesi, 2010)
Incisional hernias are most encountered complications after abdominal operations. İncidence is changing between 2-11%. The only treatment of incisional hernia is surgery. At the present day, the repair type of incisional hernia is repairing with prosthetic materials. At that point, the question of ?Which layer of abdomen do we locate the mesh?? is following. İn this study, prolene mesh located to onlay, preperitoneal and intraperitoneal layers. Amount of total collagen and the ratio of collagen type I to type III near and above the mesh in fibrotic tissue determined and compared.In this study, 40 Wistar Albino rats used. Rats categorized that control, onlay, sublay extraperitoneal (preperitoneal) and sublay intraperitoneal that all groups contains 10 rats. In rats abdomens midline, incisional hernia formed by laparotomy. Then (intraoperative), mesh which placed to the preperitoneal, intraperitoneal and onlay layers fixed with nonabsorbable sutures. All groups' and control group's incisions (linea alba) closed continue sutures and skin sutured with nonabsorbable sutures. 30 days later, skin incised previous incisions and meshes are founded. Scar tissues above and near by meshes in study groups and also on linea alba in the control group are taken. The ratio of collagen type I / III with immunhistochemically and amount of total collagen determined. In each groups, amount of total collagen and the ratio of collagen type I / III compared.When the amount of total collagen compared to control group; It was raised in preperitoneal group (p=0.000) and intraperitoneal group (p=0.000). Significant difference didn't observe in onlay group (p=0.051). Significant difference found in preperitoneal group compared to intraperitoneal group (p=0.008). When the ratio of collagen type I / III compared to control group; The ratio was raised in preperitoneal group (p=0.000) and intraperitoneal group (p=0.000). In onlay group, significant difference didn't observe (p=0.615). Significant difference found in preperitoneal group compared to intraperitoneal group (p=0.000).As a result; the mesh located to different layers is affecting the formation of collagen type I / III.

İnsizyonel herniler karın cerrahisi sonrası sık karşılaşılan komplikasyonlardan biridir. İnsidansı %2-11 arasında değişmektedir. İnsizyonel herninin tek tedavisi cerrahidir. Günümüzde en çok seçilen yöntem prostetik yama ile onarımdır. Bu noktada yamayı hangi katmana koyalım sorusu ortaya çıkar. Bu çalışmada prolen yama onlay, preperitoneal ve intraperitoneal alanlara konuldu. Yamanın üzerindeki ve çevresindeki fibrotik dokulardaki total kollajen miktarı ve kollajen tip I / tip III oranları belirlenip karşılaştırıldı.Bu çalışmada 40 adet Wistar Albino türü rat kullanıldı. Ratlar, kontrol, onlay, sublay ekstraperitoneal (preperitoneal) ve sublay intraperitoneal olarak her birinde on rat olacak şekilde gruplandırıldı. Ratların karın orta hatlarında laparotomi yapılarak kesi fıtığı oluşturuldu. Ardından (intraoperatif) onlay, preperitoneal ve intraperitoneal olarak yerleştirilen yama emilmeyen sütürlerle tespitlendi. Tüm grupların ve kontrol grubunun insizyonları (linea alba) kontinue sütürle kapatıldı ve cilt nonabsorbable sütürle dikildi. 30 gün sonra eski insizyonlardan cilt kesilip yamalar bulundu. Çalışma grubundaki ratlarda yamaların üzerinden ve kenarından, ayrıca kontrol grubunda linea albadan örnekler alındı. Örneklerde total kollajen miktarı ve immünhistokimyasal yolla kollajen tip I / III oranları belirlendi. Gruplar arasında total kollajen miktarı ve kollajen tip I / III oranları karşılaştırıldı.Total kollajen miktarı kontrol grubu ile karşılaştırıldığında; preperitoneal grupta (p=0.000) ve intraperitoneal grupta (p=0.000) artmıştı. Onlay grupta anlamlı bir fark gözlenmedi (p=0.051). Preperitoneal grupta intraperitoneal gruba göre anlamlı farklılık bulundu (p=0.008). Kollajen tip I / III oranı kontrol grubu ile karşılaştırıldığında; preperitoneal (p=0.000) ve intraperitoneal grupta (p=0.000) artmıştı. Onlay grupta anlamlı bir fark gözlenmedi (p=0.615). Preperitoneal grupta intraperitoneal gruba göre anlamlı farklılık bulundu (p=0.000).Sonuç olarak; Farklı katmanlara konulan yama kollajen tip I / III formasyonunu etkiliyor.
Is the mesh (Prolen) located to different layers in the treatment of hernia affecting the formation of collagen type i and type iii?
Keywords: Genel Cerrahi